2006
DOI: 10.1017/s0021859606006599
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Lablab purpureus accessions for crop-livestock production in the West African savanna

Abstract: The introduction and use of herbaceous legumes may contribute to agricultural intensification, especially in the context of sustainable crop and livestock production systems. In the context of evaluating different legume species for these systems in moist savanna zone of West Africa, the present study involved the evaluation of 46 accessions of Lablab purpureus (L.) Sweet between 2000 and 2002 at Samaru, Zaria in the northern Guinea savanna of Nigeria to identify accessions with the potential to contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…Of the forty six lablab accessions evaluated, fifteen accessions were suitable for vegetable pods, 11 accessions were suitable for grain-type lablab and three accessions were suitable for food-feed use (Ewansiha et al, 2007b; ) was comparable with yields obtained with other grain legumes (Ewansiha et al, 2007a; Table 3). The lablab grain had an average protein concentration of 25.3% which was comparable with protein contents reported for the dry seeds of the common grain legumes (Table 3), indicating the potential for lablab to contribute to high quality grain nutrition.…”
Section: Lablab As a Quality Food Cropmentioning
confidence: 88%
See 2 more Smart Citations
“…Of the forty six lablab accessions evaluated, fifteen accessions were suitable for vegetable pods, 11 accessions were suitable for grain-type lablab and three accessions were suitable for food-feed use (Ewansiha et al, 2007b; ) was comparable with yields obtained with other grain legumes (Ewansiha et al, 2007a; Table 3). The lablab grain had an average protein concentration of 25.3% which was comparable with protein contents reported for the dry seeds of the common grain legumes (Table 3), indicating the potential for lablab to contribute to high quality grain nutrition.…”
Section: Lablab As a Quality Food Cropmentioning
confidence: 88%
“…Lablab has a potential for up to an average of 2600 kg ha -1 of biomass and an average of 64.1 kg of nitrogen ha -1 (Ewansiha et al, 2007a; Table 4). This means that lablab has high potential for green manure and soil improvement.…”
Section: Lablab As a Resource For Crop Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several legumes studied, Cheruiyot et al (2001) reported highest increase in soil N in lablab plots, which was due to high residue quality. Ewansiha et al (2007) reported up to 184 kg N ha -1 for lablab shoot. The higher soil P and K obtained in plots planted to PI 388013 may indicate that this accession is better able to mine soil P and K from deeper soil horizons.…”
Section: Discussionmentioning
confidence: 99%
“…Lablab (Lablab purpureus [L.] Sweet), a multi-purpose legume used for food, fodder, soil improvement, soil protection and weed control (Ewansiha et al, 2007), may be grown as a component crop in mixed farming systems (NAS, 1979). In northern Nigeria, lablab provides food for humans, fodder for livestock and income from the sale of grains and fodder (Bhat and Etejere, 1985;Thomas and Sumberg, 1995;Iwuafor and Odunze, 2000;Adeoye and Onifade, 2000).…”
Section: Introductionmentioning
confidence: 99%